Enhancing Web Navigation Appropriateness by Correlating Actual and Predictable Practice (International Journal of Engineering and Computer Science, 2017)
a new method to identify navigation- related Web usability problems based on correlating Actual and Predictable usage patterns. The actual usage patterns can be extracted from Web server logs routinely recorded for operational websites by first processing the log data to identify users, user sessions, and user task-oriented transactions, and then applying an usage mining algorithm to discover patterns among actual usage paths. The anticipated usage, including information about both the path and time required for user-oriented tasks, is captured by our ideal user interactive path models constructed by cognitive ex- perts based on their cognition of user behavior. The comparison is performed via the mechanism of test oracle for checking results and identifying user navigation difficulties. The deviation data produced from this comparison can help us discover usability issues and suggest corrective actions to improve usability. A software tool was developed to automate a significant part of the activities involved. With an experiment on a small service-oriented website, we identified usability problems, which were cross-validated by do- main experts, and quantified usability improvement by the higher task success rate and lower time and effort for given tasks after suggested corrections were implemented.